Meaning in life, uncertainty, and depressive symptomatology - Morse, Jessica L., author; Steger, Michael F., advisor; Dik, Bryan J., committee member; Shomaker, Lauren B., committee member (Colorado State University. Libraries, 2017)
One important aspect of well-being, perceived meaning in life, is associated with good psychological health and reduced psychopathology (e.g. Ryff, 1989, Steger, Frazier, Oishi, & Kaler, 2006). Disposition toward uncertainty is also implicated in well-being and psychopathology. Rating uncertainty as intolerable is correlated with various forms of mental illness and distress (e.g. Koerner & Dugas, 2008; Dugas, Gosselin & Ladouceur, 2001). The current studies explore how meaning in life and response to uncertainty influence depressive symptomology in samples of undergraduate students. Study 1 examined correlations among meaning in life, intolerance of uncertainty, and depressive symptomology. In Study 2, an experiment was conducted to investigate how levels of uncertainty salience influence individuals' responses to ambiguous information and resulting depressive symptoms. Results indicated that higher levels of meaning in life significantly relate to lower levels of depressive symptoms and more tolerance of uncertainty. Study 2 explored interactions between perceived meaning in life and tolerance for uncertainty in predicting depressive symptoms based on randomly assigned uncertainty-salience conditions. Several moderation analyses supported hypotheses that presence of meaning attenuated the relationship between intolerance of uncertainty, uncertainty condition, and depressive symptoms. Explanations for the relationships found are discussed, and alternative interpretations, including the possibility that the elicitation of uncertainty prompted participants to actively make meaning of their experience, are examined.